1995
DOI: 10.1111/j.1432-1033.1995.897_a.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of tRNAPhe by Phenylalanyl‐tRNA Synthetase of Thermus Thermophilus

Abstract: The tRNAYh' nucleotides required for recognition by phenylalanyl-tRNA synlhetase of lhermus thermophilus have been determined using Escherichia roli tRNAph' transcripts with various mutations. The anticodon nucleotides are shown to be the most important recognition elements. The discriininator nucleotide, A73, involved in thc recognition sel of yeast, E. r d i and human phenylalanyl-tRNA synthetases contributes only slightly to tRNAPh' recognition by Th. tht,rrrmphilus phenylaliinyl-tRNA synthetase. Nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…The mutants (Moor et al, 1995). Nucleotides whose mutations appeared to have a very modest, if any, effect are among the contact sites in the crystal structure of the complex (Goldgur et al, 1997) or were supposed to be involved in conformational rearrangement of the complex .…”
Section: Comparison Of Binding and Aminoacylation Properties Of Trna mentioning
confidence: 99%
See 2 more Smart Citations
“…The mutants (Moor et al, 1995). Nucleotides whose mutations appeared to have a very modest, if any, effect are among the contact sites in the crystal structure of the complex (Goldgur et al, 1997) or were supposed to be involved in conformational rearrangement of the complex .…”
Section: Comparison Of Binding and Aminoacylation Properties Of Trna mentioning
confidence: 99%
“…Closely similar kinetic parameters of aminoacylation with T. thermophilus PheRS have been determined for the native T. thermophilus tRNA Phe and the E. coli tRNA Phe transcript at two MgCl 2 concentrations (9 and 15 mM); 9 mM MgCl 2 is optimal for efficient aminoacylation of both tRNAs. Mutant transcripts obtained on the background of E. coli tRNA Phe were further used to identify the tRNA nucleotides recognized by the thermophilic PheRS (Moor et al, 1995).…”
Section: E Coli Trna Phe Is An Efficient Substrate In Binding and Ammentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this system resembles various mesophilic and thermophilic systems in which post-transcriptional modifications do not participate in tRNA identity (e.g. Piitz et al, 1991 ;Nameki et al, 1992;Moor et al, 1995;Becker et al, 1996). Structural peculiarities and specificity for prokaryotic and eukaryotic tRNAG'' species.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that identity elements of a tRNA often vary during evolution (9)(10)(11)(12)(13)(14)(15)(16), although some are maintained (17)(18)(19)(20). An artificial aminoacylation system comprised of a tRNA and an aminoacyl-tRNA synthetase from different sources often causes a unilateral aminoacylation specificity and sometimes causes a lack of amino acid specificity (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%